Highly stable amorphous silica-alumina catalysts for continuous bio-derived mesitylene production under solvent-free conditions. Issue 4 (6th February 2023) - Reif, Phillip; Gupta, Navneet Kumar; Rose, Marcus
Abstract : Amorphous silica-alumina are efficient and highly stable catalysts for the continuous production of biomass-derived aromatics such as mesitylene from acetone, thus adding to the potential for value creation in biorefineries. Abstract : Aromatization of alkyl methyl ketones obtained from biorefinery streams is a viable and attractive catalytic pathway to renewable aromatics, precursors for various important monomers and chemicals. To achieve high catalytic activity and stability under continuous conditions, mesoporous amorphous silica-alumina (ASA) catalysts are studied for the acid-catalyzed self-condensation of biomass-derived acetone to mesitylene in solvent-free conditions using a fixed-bed reactor. The catalytic efficiency of ASA catalysts depends on their structure and intrinsic acidity. In comparison to pure alumina, ASA Siralox 30 exhibits a 2.2 times higher catalytic activity for acetone conversion and 3.8 times higher mesitylene yield, demonstrating the importance of Brønsted acid sites (BAS) generated in ASA catalysts. The detailed kinetic studies and catalyst characterization indicate that mesitylene formation is favored over BAS and that the formation rate is enhanced with the relative strength of BAS. We demonstrate here that Siralox 30 (total product selectivity = 66%, W / F = 12.5 gcat h mol −1 ) is an adequate and highly active catalyst for the continuous mesitylene synthesis with remarkable long-term operational stability (>50 hours-on-stream).